Opportunities for Practicing English: It Is a Matter of Picking Them up - Boonpattanaporn, Pornpan (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2014)
Speaking English has always been a major problem for Thais. Though it has been brought into focus in all educational institutions, practicing speaking in class is still often problematic. Role-plays and simulations are created to enhance students’ abilities. However, practicing in genuine real-world situations is without equal. Thailand is not an English speaking country but opportunities for practicing English are not too difficult to find. Various activities related to tourism can be designed and assigned to promote both language practice and contribution to the community. Several factors and adjustments are presented for consideration. Activities and preparation are suggested to be practically used to suit each institution’s context.